ANALISIS INTEGRASI MANAJEMEN LOGISTIK BAHAN MAKANAN TERHADAP PENCATATAN AKUNTANSI KEUANGAN UMKM PADA RUMAH MAKAN XXX - Riko Sutriyadi; Hendry Eka Sakti; M. Ferdinansyah (JURNAL LENTERA AKUNTANSI, 2025)
Financial statements serve as a vital instrument in analyzing a company's financial performance, providing a comprehensive overview of assets, liabilities, and equity positions that form the strategic foundation for economic decision-making. However, limited financial literacy and recording systems remain major obstacles for SME players. This research aims to bridge this gap by designing a computer-based accounting system specifically engineered to simplify the financial reporting process for small business owners. This research approach utilizes a quantitative descriptive method to map operational and technical needs in the field. The integration of computerized accounting aspects ensures that transaction data is not only recorded digitally but also generates accurate, real-time information with minimal risk of human error. From a business administration perspective, the implementation of this system aims to strengthen internal management governance. With structured reports, SMEs can control cash flow, manage inventory, and monitor operational expenses more professionally, thereby creating efficiency in business sustainability. Furthermore, from an international business administration perspective, technology-based standardization of financial statements is the first step for SMEs to penetrate the global market. Accountable and transparent reports make it easier for business actors to meet cross-country regulatory standards, access international financing, and build credibility in the eyes of investors and foreign trading partners.". The results of this study conclude that digital transformation in financial reporting provides tangible benefits for SMEs in determining their precise financial condition. Therefore, collective efforts are required to foster a culture of disciplined financial recording. The implications of this research are expected to formulate a concept for cultivating financial reporting that integrates sophisticated accounting technology with modern business management practices, in order to create an SME ecosystem that is resilient, accountable, and competitive on the international stage